Photoluminescence properties of ZnO thin film on sapphire substrates fabricated by ion implantation at elevated temperature and thermal oxidation - Trịnh, Thị Tú Anh (2023)
ZnO thin films on sapphire substrate were fabricated by ion implantation combined with thermal oxidation. A sapphire substrate was implanted with 50 keV zinc ions at 350 °C with a fluence of 1.5 × 1017 ions cm−2, then annealed in a tube furnace in oxygen ambient in 2 h at 650 °C. Photoluminescence spectra were collected at temperatures from 80 to 300 K to understand the optical properties of this film. The photoluminescence spectrum at 300 K included a UV peak at 377 nm and a broad peak from deep level emission at 500 nm. The fine spectra structure at 80 K consisted of the free exciton at 3.373 eV and the donor bound exciton at 3.357 eV. The first and second phonon replicas of free excitons were also observed and the origin of the deep level emission peak was clarified.